2013
DOI: 10.1074/jbc.m112.395913
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogene Metadherin Modulates the Apoptotic Pathway Based on the Tumor Necrosis Factor Superfamily Member TRAIL (Tumor Necrosis Factor-related Apoptosis-inducing Ligand) in Breast Cancer

Abstract: Background: MTDH is overexpressed in breast cancers and promotes resistance to multiple chemotherapeutic agents. We hypothesized that MTDH may contribute to TRAIL resistance in breast cancer. Results: MTDH modulated TRAIL resistance in breast cancer cells through caspase-8 down-regulation and Bcl-2 up-regulation. Conclusion:The findings uncovered novel mechanisms of TRAIL resistance mediated by MTDH. Significance: MTDH can be considered as a novel target for overcoming TRAIL resistance in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…By contrast, at 10 and 20 µM SM, the apoptosis rate was identified to be significantly different compared with the control group (P<0.001). In order to clarify the exact mechanism of apoptosis in hepatoma cells, the expression levels of Bcl-2 family proteins and caspases were examined (33,34). Bcl-2 family proteins play a crucial role in the mitochondrial apoptosis pathway, and the Bax/Bcl-2 ratio reflects a close association to the extent of apoptosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, at 10 and 20 µM SM, the apoptosis rate was identified to be significantly different compared with the control group (P<0.001). In order to clarify the exact mechanism of apoptosis in hepatoma cells, the expression levels of Bcl-2 family proteins and caspases were examined (33,34). Bcl-2 family proteins play a crucial role in the mitochondrial apoptosis pathway, and the Bax/Bcl-2 ratio reflects a close association to the extent of apoptosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…MTDH could mediate drug resistance in various cancers30 as suggested by Meng et al . For reproduction malignancies, it was reported that inhibition of MTDH increases cancer cells’ sensitivity to chemotherapy drugs, such as AZD6244, tumor necrosis factor-a-related apoptosis-inducing ligand (TRAIL) and HDAC inhibitor LBH589313233. Interestingly, Zhao Y et al .…”
Section: Discussionmentioning
confidence: 99%
“…TRAIL expression activates immune cells through thyroid autoantigen generation, in order to generate IFN-γ and TNF-α. The synergic induction of IFN-γ and TNF-α results in the expression of TRAIL by thyroid cells, increasing the sensitivity of TRAIL on immune cells, and ultimately resulting in apoptosis (27). Furthermore, TNF-α and IL-1 may result in the destruction of thyroid cells.…”
Section: Discussionmentioning
confidence: 99%
“…At present, TRAIL is considered to result in apoptosis through activation of immune cells, leading to generation of TNF-α and IL-1 (24). TNF-α and IL-1 have a synergistic effect that improves thyroid cell sensitivity of TRAIL, resulting in the death of thyroid cells (27). TRAIL expression activates immune cells through thyroid autoantigen generation, in order to generate IFN-γ and TNF-α.…”
Section: Discussionmentioning
confidence: 99%